Answer:
y = -3.3 then -7.1
y = -7.1 then -10.9
y = -2.6 then -6.4
y = 1 then -2.8
y = 4.2 then 0.4
Step-by-step explanation:
(-3.8)+0+y can be simplified to -3.8 + y. Evaluate each value for y by substituting it into the expression and solving.
y = -3.3 then -3.8 + -3.3 = -7.1
y = -7.1 then -3.8 + -7.1 = -10.9
y = -2.6 then -3.8 + -2.6 = -6.4
y = 1 then -3.8 + 1 = -2.8
y = 4.2 then -3.8 + 4.2 = 0.4
I would say: 2 times 5 less a number.
X is equal to -3.2 and y is equal to -8
Answer:
He has 5 sandwiches, 7 sides, and 10 drinks to choose from
Step-by-step explanation: